Correlations between uncertainty in illness and anxiety, depression and quality of life in patients receiving maintenance haemodialysis: A cross‐sectional study - Jingxia Cheng; Dongju Yang; Qiantao Zuo; Weixu Peng; Longling Zhu; Xiaolian Jiang (Wiley, 2022)
Abstract Aim To investigate the uncertainty in illness, anxiety, depression and quality of life in patients receiving maintenance haemodialysis and confirm the correlations between these variables. Design A cross‐sectional study was conducted among 396 patients receiving maintenance haemodialysis in four tertiary hospitals in China. Methods Uncertainty in illness was measured by Mishel's uncertainty in illness scale. The scores of self‐rating anxiety scale, self‐rating depression scale and medical outcomes study short form 36 were collected and compared with available norms. The Pearson correlation coefficient was calculated to investigate the correlation between uncertainties in illness with these vital variables. Results The mean score of uncertainty in illness was 78.16 out of 160. Compared with the norm, patients receiving maintenance haemodialysis had a statistically significantly lower score of depression and higher scores of most domains of quality of life. Uncertainty in illness is corrected with anxiety, depression positively and with quality of life negatively.